Heat Transfers Analysis Of Car Radiator For CoolingSystem Of Toyota Rush 1.5 M/T - SINURAT, DAVID (2011)
Although gasoline engines have improved a lot, they are still not very efficient at turning chemical energy into mechanical power. Most of the energy in the gasoline (perhaps 75%) is converted into heat, and only 25% of total energy produced in gasoline engine which converted into effective work. Therefore, it is the job of the cooling system to take care of that heat. The objectives are to investigate heat transfer rate through radiator and create simple segment analysis which then compared to full radiator analysis. Cooling systems are designed to allow the engine to reach a normal operating temperature as soon as possible and then maintain that operating temperature over the course of driving in a wide range of ambient temperature ranges and finally, to prevent any overheating that might occur. Coolants in the closed loop system are designed to absorb engine heat and transfer it to the radiator so that through convection and thermodynamics heat transfer may occur. A radiator is a type of heat exchanger. It is designed to transfer heat from the hot coolant that flows through it to the air blown through it by the fan. In order to obtain the result, it is important to know inlet and outlet temperature of radiator and air which passing through radiator. Total heat transferred by car radiator is vary depend on speed of vehicle which will affect air flow speed through radiator. When thermostat opens total heat transferred by radiator is 13274.61 Btu/hr. Segment analysis for radiator when thermostat opens is 15842.1 Btu/hr. Therefore, heat transfer efficiency of car radiator of Toyota Rush 1.5 M/T is 83.6%.